ANALISIS TINGKAT KELENGKAPAN DAN KETEPATAN WAKTU PENGEMBALIAN BERKAS REKAM MEDIS RAWAT JALAN DI PUSKESMAS PERAMPUAN TAHUN 2022 - Evhia Rizqiana; I Made Putu Sudiartha Hartawan (Nusadaya Journal of Multidiciplinary Studies, 2022)
Every health care institution must have a medical record file. The medical record contains the records and documents on the identity of the patient, examination, treatment and subsequent actions. This study aims to determine whether there is an effect on the completeness and timeliness of returning outpatient medical record files on the quality of service at the Perampuan Community Health Center in 2022. This study used a descriptive quantitative method with a population of outpatient medical record files with a sample of 100 medical record files. The results of this research at the Perampuan Health Center found incompleteness as well the incompleteness in the time to return medical record files. It shows that Complete (74.0), Incomplete (8.0) and less complete (18.0) medical record filling. The return of the medical record file was not on time /<1x24 hours (83.0) and the return of the medical record file was not on time /> 1x24 hours (17.0).